MY STORY - Rizki Ramadhan; Syeilendra Syeilendra; Yos Sudarman (FBS Universitas Negeri Padang, 2017)
The purpose of this work was to narrate the author's life story by using a violin as the instrument. It told about the author's love of this cord instrument. Through the work of